Mediating Faith : Faith Tranformation in a Trans-media Era - Schnekloth, Clint (Book collections on Project MUSE., 2014)
The church struggles with media. Whether it is a denomination negotiating the 24-hour news cycle or a church evaluating how Facebook or online games are influencing the youth group, media is raising questions and placing demands on communities of faith in ways that could not have been imagined just 20 years ago. Thus the importance of understanding media for the church has never been greater. In Mediating Faith, church leaders of all kinds will find Clint Schnekloth an engaging and insightful guide to this new and sometimes wondrous world. In doing so he offers an evaluation and theological response to the trans-media era that highlights its potential to transform our work and world.Far from frightening, Schnekloth highlights the opportunities and the riches of this fascinating time.